Strategic Analysis of PT Bank Perkreditan Rakyat (BPR) Citra Dana Mandiri - Nurul Pratiwi Hadi; Ayi Ahadiat (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesians are realizing the importance of safe and profitable savings. Thus, bank investment considerations are rising. People invest in People's Credit Banks (BPR) instead of traditional banks. Additionally, BPR provides village loans. Rural Banks (BPR) have helped many SMEs. This study examines PT. People's Credit Bank (BPR) Citra Dana Mandiri's external and internal environment and determines its best alternative strategy. IFE, EFE, SWOT, IE, and QSPM analysis tools are used in this study. Non-performing loans and market share were PT BPR Citra Dana Mandiri's biggest internal strengths. PT BPR Citra Dana Mandiri's biggest weakness was its lack of mobile-banking and 2 branch offices. Vehicle enthusiasts are a major external factor. the growth of MSMEs in Lampung Province, with competitors aggressively pursuing market share and offering credit and facilities. The TAS/Total Activeness Score QSPM, the first strategic alternative PT BPR Citra Dana Mandiri prioritizes, is market penetration. Market penetration can estimate PT BPR Citra Dana Mandiri's potential market